APPLICATION OF WILD CARD TECHNIQUES TO TEACH WRITING DESCRIPTIVE TO THE FIRST GRADERS OF JUNIOR HIGH SCHOOL (RETAIN, 2014)
APPLICATION OF WILD CARD TECHNIQUES TO TEACH WRITING DESCRIPTIVE TO THE FIRST GRADERS OF JUNIOR HIGH SCHOOL Fitrianti Wulandari, Dr.Oikurema Purwati, M.Appl English Education Program, Faculty of Languanges and Arts Surabaya State University Fitriantiwulandari@ymail.com ABTRACT This research is aimed to describe the application of wild card techniques to teach writing descriptive to the first graders of junior high school and to describe the students’ result after the application. The design of this research is a qualitative research. To conduct the research, a field note is used as an instrument which components are descriptive part and reflective part. The research subjects are the students of 26 Junior High School Surabaya, especially the students of VII G Class. The result of this research is that the application of wild card to teach writing descriptive was conducted properly according to the framework suggested by Willis and was very engaging and motivating the students. Students’result after the application of wild card language teaching on the first and the second meeting were averagely good. Since it was not a classroom action research, the research was not aimed to improve the students’ result. Keyword: wild card, application of wild card technique, writing, descriptive, junior high school. ABSTRAKSI Tujuan dari penelitian ini adalah untuk menjelaskan tentang tehnik wild card untuk mengajar di kelas pertama sekekolah menengah pertama dan untuk menjelaskan tentang hasil dari pengaplikasian tehnik tersebut. Desain penelitian ini adalah penelitian kualitatif. Untuk mendukung jalannya penelitian ini, peneliti menggunakan field note sebagai instrumentnya. Dengan bagian dari field note yang berisi deskripsi dan refleksi. Subjek peneliti adalah murid kelas VII G SMPN 26 Surabaya. Hasil dari penelitian penerapan wild card untuk mengajar writing descriptive sangat mengacu pada framework menurut teori dari Willis. Sangat memotivasi para murid. Hasil penelitian setelah penerapan wild card di pertemuan pertama dan kedua sangatlah memuaskan. Tapi ini bukanlah penelitian tindakan kelas, karena penelitian ini tidak bertujuan untuk meningkatkan hasil siswa. INTRODUCTION English as an international language plays an important role in human being civilization in recent days. Mastering English is very important to support people’s communication in this era. Anywhere people want to connect, the language mostly used is English. Communication itself can be separated into two, they are written and oral communication. people learn spoken language first before they learn written version, but not all people can communicate their ideas orally. To overcome this problem, written communication becomes the alternative for those who have difficulties in communicating orally. Therefore, students need to learn how to write in proper way. written language is more understandable than spoken language. This happens when the speaker speaks too fast or not clear in pronunciation or vocalization. It makes the listener difficult to understand what the speaker speaks. many Junior High School students often face difficulties in learning writing. They consider that writing is a complex skill, they must think about their ideas and they must write their ideas in English appropriately at the same time. So, the teacher should give more exercises to the students in order to develop their writing skill especially in nmaking a text (genre) because there are many genres that must be learned by Junior High School Students. In writing functional texts, they can learn how to write many kinds of texts, such as descriptive, narrative, recount, procedure, report, etc. Type of texts which is going to be discussed in this study is descriptive text. descriptive text is taught in the second graders of junior high school (basic competence no. 12.2) it seems writing descriptive text is the simplest and easiest for the students still get difficulty in how to start writing because they lack of idea. The teachers should use the available aids to make the students enjoy in learning the descriptive text. A wild card is one of the interesting teaching aids. According to Collins stated that a wild card is an interactive way to motivate students in their writing and discussion. This card consist of some jumbled sentences which should be arrange by the students becomes a good paragraph. It means that a wild card is one of teaching aids that can be used by the teachers in teaching learning process (1998). According to the Lindstomberg (2004), wild card technique previously known as kill the text. This teechnique uses complete sentences that have been cut into several parts according to the sentence subject, predicate and complement. In indentifying the subject of the sentence, students will learn about nouns generally occupy the predicate position. The latter students will learn about the modifier, adverb, adjective, complementary group which usually occupy complementary positions. This technique can help teachers introduce English nouns, adjectives, and verbs in the descriptions text. So the students do not have to learn a lot of adjectives and objects separately. In addition, students can learn about simple sentences when they combine the seperate parts becomes a complete sentence. According to Ellis (2006), there are three stages in applicating wild card techniques in a classroom, which they are the pre-activity stage, the during the stage, and the last stage. When the pre-activity, the teacher asked the student to make a group then the teacher gave the group about the topic. Each group had different topic. After that the teacher gave them the wild card. In the during the activity, the teacher gave time to the students to finished the wild card. Here, the students have to arrange jumbled sentences becomes a good paragraph. In the last activity, the students must show the result of wild card in front of the class. This technique was effective to engage and motivate the students to learn writing descriptive actively. A wild card is simply a collection of items in card that corresponds to the jumbled paragraph. It is still rarely used by the teachers in teaching learning of descriptive text. Most of teachers use picture as media when they teach descriptive text. Based on the explanation above, the researcher would like to conduct a study on the use of a wild card as media for teaching writing descriptive text for the eighth graders of junior high school of SMPN 26 Surabaya. The researcher chooses that school because SMPN 26 Surabaya is facilitated with card as media when the teacher teaches descriptive text. By means of the facilitation, the researcher tries to use wild card in teaching writing descriptive text. By doing this study, the writer hope this study can be useful for the writer, students, and the teachers of English language. Students This study can encourage and stimulate the students to improve their ability in producing written texts properly. They will have another strategy to generate and organize thought and ideas. They will be easy to prevent the writers’ block of having the bound of idea that they want to write. And this study will make them know that wild card is not only for games but also for writing. Teachers This study can make teaching writing become easier. Teachers will have another way in giving instruction to students in teaching writing. And it will also add the varieties of strategies in teaching writing. The writer This study will prove that wild card can be used for other purposes, such as writing. This study focuses on the application of wild card techniques in the first grade of 26 State Junior High School Surabaya. The research was conducted by observing and describing the application of wild card techniques done by the teacher of the first grader of junior high school. The findings do not discuss about the advantages or disadvantages of wild card techniques. This study also focuses on students’ writing ability, especially in writing descriptive. To avoid misunderstanding and gain the same perception, the researcher provides the following key terms. A wild card is simply a collection of items in a card that corresponds to the jumbled paragragraph. (Collins, 2008: 117) Writing is visual representation of thoughts, feelings, and ideas using symbols of the writer’s language system for the purpose of communication or recording (Poteet, 1992: 231) A descriptive text is a text which says what a person or a thing is liked and lists the characteristics of something. Its pursose is to describe and reveal a particular person, place or thing. (Pullock, 1995: 217). As a way of communication, the main purpose of writing activity is to communicate in a written form. It is a communication between the writers and the readers. That is why, writing means telling what the writers think to the others. The writers express the idea through writing, and this writing requires many complicated things in the proces. Writing as a process can be defined as a complex system people use when transcribing ideas into written forms (Stone.1994). Writing is essential in academicals fields. Writing mastery during school time is a must, since it will facilitate students to learn other skills as well. Abbot (1981:143) said that there are good psychological and practical reasons why writing should be integrated with other language skills. Even where the main goal is spoken skill is some academic areas, writing can be a great assistance. It implies that writing will reinforce other skills, such as reading, listening, and speaking because students’ range of vocabulary and structure will be increased automatically. Additionally, Harmer (2001) also says that in the teaching of writing, it can be focused on the product, writing activity is stressed in the aim of a task. Expressing ideas in the writing process has four stages, they are: Prewriting: Prewriting is any kind of experience or activity that motivates a person to write. It uses a variety of active experience to expand ideas and to help writers organize their ideas before they begin to write. Writing: This is the step where ideas are recorded on the paper. The focus in writing is to write frequently, expressing ideas quickly with little concern for correctness. The writers need to understand that the first draft is for synthesizing thought and ideas form the prewriting experience. The writers are also need to be given frequent opportunities to do all kinds of writing and to have specific purpose for writing. Responding: Responding allows person to get reaction from other person on what they have writen. The responses are usually given in the form of statements, questions, or suggestions and can be given orally or in the writen form. The responses also provide guidance to the writers in clarifying their writing. Revising: In this revising process, the writers receive comments from others. This is a step where the writers can delete, add or change the ideas but not to correct it. Writing also can help someone to solve the problems, to understand the other things better, and to communicate with other clearly. Dealing with that uniqueness, Stratta et.al (1973: 15) states the basic creative process is one that describe as the discovery of uniqueness. The writer discovers his own uniqueness, he discovers the uniqueness of words to express the uniqueness of mind, and he discovers the uniqueness of form that is chosen a result of the nature of the uniquness. Thus, writing can help the writer to understand himself better too. In other words, people will feel better when they can express their mind in a form of writing. Descriptive is a piece of text that describes a particular person, place, or thing. It is also used in all forms of writing to create vivid impression of a person, place, object or event. Its purpose is to tell about the subject by describing its feature without including personal opinions. The purpose of descriptive test also emphasize by Hyland (2002:20). He states that the purpose of descriptive is to give an account of imagined, factual events and phenomena. That is why, by imagine and investigate in depth something being described by the writer, the listener or the readers can visualize the topic and enter the writer’s experience. Descriptive, basically, concentrates upon words relate to human sense, such as sight, sounds, and smells. As Pullock (1995:217) says that people have to be conscious of sight, smells and sounds when they are outdoors. He also says, there are two things required to write good descriptive paragraph; (1) observing as many details as you can, and (2) selecting the one that give clearest picture. Through the concrete picture, readers can find the description more meaningful. The generic structure of descriptive text are identification or definition and description. The language features according to Mursyid (2011) is Descriptive often uses ‘be’ and ‘have’. Tense which is often used is simple present tense. However, sometimes it uses past tense if the thing to be described does not exist anymore. A wild card is one of the interesting teaching aids. According to Collins stated that a wild card is an interactive way to motivate students in their writing and discussion. This card consist of some jumbled sentences which should be arrange by the students becomes a good paragraph. It means that a wild card is one of teaching aids that can be used by the teachers in teaching learning process (1998). Wild Card technique previously known as Kill the Text (Lindstromberg, 2004:52). This technique uses complete sentences that have been cut into several parts according to the sentence subject, predicate and complement. In identifying the subject of the sentence, students will learn about nouns generally occupy the subject. Later in the article, students will learn about verbs that generally occupy the predicate position. The latter students will learn about the modifier, adverb, adjective, complementary group which usually occupy complementary positions. According to Ellis (2006), there are three stages in applicating wild card techniques in a classroom, which they are the pre-activity stage, the during the stage, and the last stage. When the pre-activity, the teacher asked the student to make a group then the teacher gave the group about the topic. Each group had different topic. After that the teacher gave them the wild card. In the during the activity, the teacher gave time to the students to finished the wild card. Here, the students have to arrange jumbled sentences becomes a good paragraph. In the last activity, the students must show the result of wild card in front of the class. This technique was effective to engage and motivate the students to learn writing descriptive actively. This technique can help teachers introduce English nouns, adjectives, and verbs in the description text descriptions so that students do not have to learn a lot of adjectives and objects separately. In addition, students can learn about simple sentences when they combine the separate parts so that it becomes a complete sentence. In the depiction of the home, students will recognize the shape, color, size, number, origin of manufacture of an item and how to recognize the goods or location. Everything can be summed up in a few sentences simple pre-prepared and in a state of incomplete cut. Student task is to find pieces that fit its original state, forming a simple sentence as before. Clipped sentences presented in the form caption depiction of a house so that when students are able to find the right pieces will be obtained correctly structured sentences and thank the grammatical English and also get a text description of the depiction. This technique can be done in groups or individuals in order to enable them to complete the essay. This study is descriptive qualitative. According to Freeman and Long (1991:11) that the descriptive qulitative is the study which is designed to identify and describe the observed phenomena in the form of words rather than in number. In this study, the researcher studies the application of wild card technique in writing descriptive text at the seventh grade students of junior high school. The researcher also gives the questionnaire to the students. Then, the researcher analyzes and describes the data in the form words. She describes the natural setting that is the real situation which happens in the class and also analyzes the students’ composition in a desciptive way. RESEARCH DESIGN This study is descriptive qualitative. According to Freeman and Long (1991:11) that the descriptive qulitative is the study which is designed to identify and describe the observed phenomena in the form of words rather than in number. In this study, the researcher studies the application of wild card technique in writing descriptive text at the seventh grade students of junior high school. The researcher also gives the questionnaire to the students. Then, the researcher analyzes and describes the data in the form words. She describes the natural setting that is the real situation which happens in the class and also analyzes the students’ composition in a desciptive way. RESEARCH INSTRUMENT The researcher will use a field note as an instrument to conduct the research. Field notes contain everything that the researcher will be seen. It has two components. They are descriptive part and reflective part. The descriptive part includes a complete description of the setting, the people, and their reactions and interpersonal relationships, and account of events (Ary, Jacobs et al. 2010). Whereas the reflective one, stated by Ary et. al (2010), includes the observer’s personal feelings or impressions about the events, comments on the research method, decisions and problems, records of ethical issues, and speculations about data analysis. Field notes may include photographs and picture. DATA COLLECTION TECHNIQUE The data collected will be a qualitative data. During the research, the researcher will do a non-participant observation as a technique to collect the data needed to answer the research questions. Non-participant observation is less subjective which latter involves observing actions and interactions, perhaps sitting in a corner of the room, silent, but attentive (Koshy 2005). DATA ANALYZING Miles and Huberman in Koshy (2005) suggest three process of analyzing qualitative data, which are data reduction, data display and conclusion drawing/verification. Data reduction refers to the process of selecting, focusing, simplifying, abstracting and transforming the data that appear in the written up field notes or transcriptions Koshy (2005). Data displays can include different types of graphs, charts and networks which purpose is to make organised information into an immediately available, accessible, compact form. Finally, the researcher draws a conclusion explicitly. RESULT AND DISCUSSIONS In this part, the researcher describes the observation result of application wild card techniques to teach writing descriptive text to the seventh graders of 26 Junior High School Surabaya. The researcher used an observation list as an instrument of the research to collect the data. The observation was conducted in class VII G in 26 Junior High School Surabaya. There were two meetings which were conducted on the 25th and 27th of November 2013. The time allocated was 2x40 minutes. The researcher attended the class was not as the teacher but as an observer of the research. The research observed the whole activities and behavior occurred in the class done by both the teacher and the students. The research wrote all the teaching-learning process in the class from the beginning until the end on a piece of paper which is called a field note. The Students’ Writing Result after the Application of Wild Card Technique In this part, the researcher elaborated the students’ result of writing ability from the two meetings. The students’ writing were used to identify their achievement. The researcher analyzed the students’ individual writing ability based on Brown and Bailey Analytical Scores for Rating Composition Tasks ( 2004:244-245 ) The components of ESL writing proficiency are orgnization, grammar, vocabulary, and content. 4.1.2.1 First Meeting On the first meeting, students were asked to do a task in group. Each group had to describe a picture they got from the teacher and write their reports in front of the class on the whiteboard. After that, the teacher asked the students wrote what they had said on the whiteboard. Group One My Classroom This is my classroom. My classroom is orderly. (Student 1). There are three pens colors purple, green, and pink. There are three pictures. (Student 2). There is one ruler. There are two erasers of soft. (Student 3). There are six chairs made from wood for students. There is one cupboard at the corner of class. (Student 22). There is a vase pretty. There are seven tables. There is one book above a table. (Student 2). From the transcript we can see that group one made only few mistakes. Student 22 gets the highest score because she made almost no mistakes. Her grammar and vocabulary were very good. She could even write very fastly. It seemed that she could comprehend every word she said although her organization is not perfect. Her score was 4 for organization, and 5 for grammar, vocabulary, and content. The second writer from group one was Student 2. She made a little mistake by writing “there are three pens colors purple, green, and pink” which is grammatically wrong. She should have written “there are three pens. They are purple, green, and pink”. It would have been correct. Her organization was good enough so she got 4 for her orgnization. Because she made a little bit mistakes grammatically, she also got 4 for grammar. Her vocabulary and content were also good enough that she got 4 for each component. The next writer were Student 1 and Student 3. Their organization was good enough that they got 4 for it. However her grammar, vocbulary, and, content were not good that she got 3 for each component. One of them wrote “There are two erasers of soft” which was grammatically wrong. She should have wrote “There are two soft erasers”. 4.1.2.2 Second Meeting On the second meeting, the teacher asked the students to gather in some groups. Each group had to finish arranging a sentences which had a wild card on it. The teacher let each group to compete each other to finish the wild card. Here is the group which had finished arranging the wild card first: Number Name Works 1 Student 4 I have a nice a classroom. My classroom is located in the corner of my school. 2 Student 5 In the classroom there are tables, chairs, white boards, lamps, cupboard. There are twenty tables in the my classroom. There are forty chairs in the my classroom. 3 Student 6 The fan is above the floor. The picture of president is above the whiteboard. Although it is small. I love my classroom so much. Student 4 got 4 for each writing content. Her organization was good. Although she made a little bit mistakes in case of grammar, but it didn’t obscure the meaning, that she got 4 for it. Her vocabulary, grammar, and contenr were also good. Student 5 was the second writer. Fortunately, his organiztion, grammar, vocabulary, and content were good. He could organize well. He made a little bit mistakes by writing “In the classroom there are tables, chairs, white boards, lamps, cupboard” This is grammatically wrong because there were cupboard. He should have said “and there is a cupboard.” Fortunately, it didn’t obscure the meaning. That’s why he got 4 for grammar. The third writer was Student 6. His organization was good. Although he made a little bit mistakes in case of grammar, but it didn’t obscure the meaning, that he got 4 for it. His vocabulary, grammar, and contenr were also good. The Discussion of the Observation In this part, the researcher will discuss the result of the observation in the relation of theory. 4.2.1 The Application of Wild Card Techniques On the first meeting, in the pre-activity stage, the teacher organized the students to make some groups. There were six groups consisted of five students, while the other one consisted of five students.. The teacher instructed each group to describe parts of a house they saw on their books. There were eight parts of a house in the book. The teacher explained about the definition and the characteristics of a descriptive text. The teacher also explained a little bit about the simple present tense, the use of “there is” and “there are”, articles ‘a’ and ‘an’, and singular and plural nouns. The students were so quiet and enthusiastic to listen to the teacher’s explanation. In the second stage or during stage, the teacher gave the students fifteen minutes to think about what they were going to write to describe the picture. Before letting the students did the group discussion, the teacher had stated that the teacher would not help them at all. The students should work themselves. This is in line to what Willis suggests. According to Willis (1996), in this stage, teachers shouldn’t help the students. Teachers should let them work themselves to construct the sentences and the language expression they would use. In the last stage, the teacher evaluated the students’ work in front of the class. The teacher called the group one by one to come forward and write their works on the whiteboard. Every member of the group took turn to describe the picture he/ she got at least two sentences. This is done so the other students could see their friends work and then evaluate what might be incorrect. On the second meeting, in the pre-activity stage, the teacher reviewed the lesson on the previous meeting. On this meeting, the teacher explained a little bit more about the simple present tense. The teacher explained about verbal and nominal sentences of the simple present tense. After that, the teacher remarked that they would conduct a wild card game. Next, the teacher mentioned some conditions while playing the game that the students should play fairly, use English when interacting, and finish the game in five minutes. Next, the teacher divided the class into seven groups. The teacher instructed the each group to make circle. After that, the teacher distributed the wild card to each group. In during stage, the wild card game started. The teacher moved around the class and observed the students. Like always, the teacher, asked the students to speak in English while solving the game. In the last stage, the teacher called each group to come forward to write their works. Each member of the group had to arranged well the sentences in the wild card. When the student was describing the picture, the teacher circle any mistakes and errors made by the student. After that, the teacher conducted an evaluation towards the students’ works. In conclusion, what the teacher did on the first meeting and the second meeting were all in line to the framework of application wild card techniques suggested by Ellis. According to Ellis (2006) there are three stages in applicating wild card techniques in a classroom, which they are the pre-activity stage, the during stage, and the last stage. When the pre-activity, the teacher asked the student to make a group then the teacher gave the group about the topic. Each group had different topic. After that the teacher gave them the wild card. In the during the activity, the teacher gave time to the students to finished the wild card. Here, the students have to arrange jumbled sentences becomes a good paragraph. In the last activity, the students must show the result of wild card in front of the class. This technique was effective to engage and motivate the students to learn writing descriptive actively. The teacher also understood the notion of the task given to the students. The task was designed not only to be completed, but also to reach the communicative purpose in order to achieve an outcome Willis (1996). It can be seen from the first and the second meetings that all of the students tried to not only complete the task given by the teacher, but also produce the language. The Students’ Writing Result after the Application of Wild Card Techniques. There are 24 students in the first meeting. They did not really know how to describe something or place well. They lack of the organization, grammar, vocabulary and content. They did not get the text before. At the first they felt confusied but after the teacher explain little by little, some of them understood about describing text but some of them not really know. On the first meeting there are 3 students got good in organization, 2 students got good in grammar, and a student got good in vocabulary and content. For very good, there are 3 students got very good in organization, 3 students also got very good in grammar, 2 students got very good in vocab and 4 students got very good in content. For perfect, there are 2 students got perfect in grammar and 2 students got perfect in content. And this is the result : Organization is 3.78 from 4. It means that most of the students’ organization is very good. Grammar is 4.36 from 4. It means that most of the students’ grammar is very good. Vocabulary is 4.27 from 4. It means that most of the students’ vocabulary is very good. Content is 3.96 from 4. It means that most of the students’ content is very good. There are five students who were absent in the second meeting. There are nineteen students in the classroom. The condition was different with the first meeting. On the second meeting, the students more entusiasthic and attractive because of wild card game. Some of them said that they prefer study with game. They taught that with game, the teaching learning process becomes fun and enjoyful. Almost all of them understood how to write description text well. On the second meeting there are 7 students got very good in organization. 4 students got very good in grammar, a student got very good in vocabulary ans content. For perfect, there are 6 students got perfect in organization, 3 students got perfect in grammar and 2 students got perfect in vocabulary. Here is the result : Organization is 3.93 from 4. It means that most of the students’ organization is very good. Grammar is 3.83 from 4. It means that most of the students’ grammar is very good. Vocabulary is 3.46 from 4. It means that most of the students’ vocabulary is good. Content is 3.4 from 4. It means that most of the students’ content is good. CONCLUSIONS AND SUGGESTIONS Conclusion According to this research, it is concluded that: The application of wild card technique to teach writing descriptive to the first graders of junior high score was conducted properly according to the framework suggested by Ellis. application was effective to engage and motivate the students to learn written descriptive actively. The students’ result after the application on the first and the second meeting were averagely good. Most of the students got good scores in writing descriptive. Suggestions From the result and the discussion, the researcher has some suggestion to teacher and the other researchers. Hopefully, the suggestion could help in the future research and studies. Wild card can be used for making writing descriptive easier. The teachers have to explain the use of wild card and how to arrange wild card into a paragraph. The teachers have to explain the generic structure of the next out of the technique used in the teaching learning activity. For the next researchers, this method could be applicated in different grades, skills, and themes. REFERENCES Ary, D., L. C. Jacobs, et al. (2010). Introduction to Research in Education. Belmont, USA, Wadsworth Cengage Learning. Ellis, R. (2006). "The application of wild card technique." Asian EFL Journal 8(3). Freeman, D. L. (2000). Techniques and Principles in Language Teaching. Oxford, Oxford University Press. Koshy, V. (2005). Action Research for Improving Practice. London, Paul Chaoman Publishing. Willis, J. (1996). A framework for wild card technique, Pearson PTR. Lindstromberg, S. (Ed.). (2004). Language Activities for Teenagers. Cambridge: Cambridge University Press. Poteet (1992). Grammar, Writing, and Technology: A Sample Technology-supported Approach to Teaching Grammar and Improving Writing for ESL Learners. CALICO Journal, 23(2), 23. Nunan, D. (2008). Research Methods in Language Learning. Cambridge: Cambridge University Press. Reid, J. (Ed.). (2008). Writing Myths: Applying Second Language Research to Classroom Teaching. Ann Arbor: University of Michigan Press. Pullock, J. (1995). Explicit Teaching of Grammar and Improvement in the Grammar of Student Writing.Journal for Language Teaching, 35(4), 16. Priyana (2008). Metodologi Penelitian Kualitatif. Edisi Revisi. Bandung: PT. Remaja Rosdakarya. Liu, Y. (2009). "What am I Supposed to Say?" --ESL Students' Expectation of Writing Conferences. 99 Arizona Working Papers in SLA and Teaching, 16, 22.